Regional target loads of atmospheric nitrogen and sulfur deposition for the protection of stream and watershed soil resources of the Adirondack Mountains, USA. (15th July 2021) - McDonnell, T.C.; Driscoll, C.T.; Sullivan, T.J.; Burns, D.A.; Baldigo, B.P.; Shao, S.; Lawrence, G.B.
Abstract: Acidic deposition contributes to a range of environmental impacts across forested landscapes, including acidification of soil and drainage water, toxic aluminum mobilization, depletion of available soil nutrient cations, and impacts to forest and aquatic species health and biodiversity. In response to decreasing levels of acidic deposition, soils and drainage waters in some regions of North America have become gradually less acidic. Thresholds of atmospheric deposition at which adverse ecological effects are manifested are called critical loads (CLs) and/or target loads (TLs). Target loads are developed based on approaches that account for spatial and temporal aspects of acidification and recovery. Exceedance represents the extent to which current or projected future levels of acidic deposition exceed the level expected to cause ecological harm. We report TLs of sulfur (S) and nitrogen (N) deposition and the potential for ecosystem recovery of watershed soils and streams in the Adirondack region of New York State, resources that have been less thoroughly investigated than lakes. Regional TLs were calculated by statistical extrapolation of hindcast and forecast simulations of 25 watersheds using the process-based model PnET-BGC coupled with empirical observations of stream hydrology and established sensitivity of sugar maple ( Acer saccharum ) to soil base saturation and brook trout ( Salvelinus fontinalis ) to stream acid neutralizing capacity (ANC). Historical impacts and the expected recovery timeline of regional soil and stream chemistry and fish community condition within the Adirondack Park were evaluated. Analysis suggests that many low-order Adirondack streams and associated watershed soils have low TLs (<40 meq/m 2 /yr of N + S deposition) to achieve specified benchmarks for recovery of soil base saturation or stream ANC. Acid-sensitive headwater and low-order streams and watershed soils in the region are expected to experience continued adverse effects from N and S deposition well into the future even under aggressive emissions reductions. Watershed soils and streams in the western Adirondack Park are particularly vulnerable to acidic deposition and currently in exceedance of TLs. The methods used for linking statistical and process-based models to consider chemical and biological response under varying flow conditions at the regional scale in this study can be applied to other areas of concern. Graphical abstract: Image 1 Highlights: Acidic deposition threatens terrestrial and aquatic species health and biodiversity. Recovery to pre-industrial conditions is not expected well into the future. Target loads are in exceedance for much of the western Adirondack Park. Abstract : Target loads of atmospheric nitrogen and sulfur deposition were determined for maintaining healthy forest and stream ecosystems in the Adirondacks. Widespread exceedances were found for both soil and streams.